Współwystępowania bólu głowy i kręgosłupa oraz objawom im towarzyszącym- badanie pilotażowe = Co-occurrence of headaches and back pain and associated with them symptoms - Katarzyna Kożuch; Piotr Kozłowski; Magdalena Kozłowska; Barbara Cuch (Journal of Education, Health and Sport, 2016)
Kożuch Katarzyna, Kozłowski Piotr, Kozłowska Magdalena, Cuch Barbara. Współwystępowania bólu głowy i kręgosłupa oraz objawom im towarzyszącym- badanie pilotażowe = Co-occurrence of headaches and back pain and associated with them symptoms. Journal of Education, Health and Sport. 2016;6(9):433-441. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.153863